In vitro and in vivo anti-Helicobacter pylori activity of Casearia sylvestris leaf derivatives. (6th April 2019) - Spósito, Larissa; Oda, Fernando Bombarda; Vieira, Júlia Hunger; Carvalho, Flávio Alexandre; dos Santos Ramos, Matheus Aparecido; de Castro, Rogério Cardoso; Crevelin, Eduardo José; Crotti, Antônio Eduardo Miller; Santos, André Gonzaga; da Silva, Patrícia Bento; Chorilli, Marlus; Bauab, Taís Maria
Abstract: Ethnopharmacological relevance: The number of bacterial strains that are resistant to multiple conventional antimicrobial agents is increasing. In this context, natural products have been widely used as a strategy to treat diseases caused by bacteria. Infections by Helicobacter pylori have attracted attention because they are directly related to severe gastric medical conditions. Casearia sylvestris Swartz, popularly known as guaçatonga, is largely employed to treat gastric disorders in Brazilian folk medicine. This plant species has aroused much interest mainly because it displays anti-inflammatory activity and can act as an antiulcer agent. Aim of the study: To evaluate the in vitro and in vivo anti- H. pylori action of C. sylvestris leaf derivatives incorporated or not in a nanostructured drug delivery system. Materials and methods: The essential oil (obtained by hydrodistillation) and ethanolic extract (obtained by maceration) were obtained from C. sylvestris leaves. The ethanolic extract was submitted to fractionation through solid phase extraction and column chromatography, to yield the ethanolic fractions. Hydrolyzed casearin J was achieved by submitting isolated casearin J to acid hydrolysis. The derivatives were chemically characterized by nuclear magnetic resonance (NMR), gas chromatography (GC), and gas chromatography-mass spectrometry (GC–MS) analyses. A nanostructured lipid system was used as drug delivery system. To assess the in vitro antibacterial activity of C. sylvestris leaf essential oil, ethanolic extract, and derivatives, microdilution, biofilm, and time-kill assays were performed against H. pylori ATCC 43504. Finally, the in vivo action was investigated by employing male Wistar rats experimentally infected with H. pylori . Results: Many C. sylvestris leaf derivatives presented significant in vitro activity against H. pylori . Among the derivatives, fraction 2 (F2) was the most effective. In vivo tests showed that both the ethanolic extract and F2 decreased the ulcerative lesion size, but only the ethanolic extract eradicated H. pylori from the gastric lesions. Incorporation of plant derivatives in nanostructured lipid system blunted the in vitro action, as demonstrated by the microdilution assay. However, this incorporation improved the ethanolic extract activity against biofilms. Conclusion: C. sylvestris leaf derivatives are effective against H. pylori both in vitro and in vivo . According to phytochemical analyses, these derivatives are rich in terpenoids, which could be related to the anti- H. pylori action. Synergism could also underlie C. sylvestris efficacy judging from the fact that the sub-fractions and isolated compounds had lower activity than the extract. Incorporation in a nanostructured lipid system did not improve the activity of the compounds in our in vivo protocol. Graphical abstract: fx1